Cognitive Informatics and Soft Computing Proceeding of CISC 2017 - Mallick, Pradeep Kumar; Balas, Valentina Emilia; Bhoi, Akash Kumar; Zobaa, Ahmed F.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
The book presents new approaches and methods for solving real-world problems. It offers, in particular, exploratory research that describes novel approaches in the fields of Cognitive Informatics, Cognitive Computing, Computational Intelligence, Advanced Computing, Hybrid Intelligent Models and Applications. New algorithms and methods in a variety of fields are also presented, together with solution-based approaches. The topics addressed include various theoretical aspects and applications of Computer Science, Artificial Intelligence, Cybernetics, Automation Control Theory and Software Engineering.
Multi-Tumor Detection and Analysis Based on Advance Region Quantitative Approach of Brest MRI -- A Secure and Computational Efficient Multicast Key Distribution for Wireless Networks -- Data Mining Approaches for Correlation and Cache Replacement in Wireless Ad Hoc Networks -- An approach to detect an image as a Selfie using object recognition methods -- T wave Analysis: Potential Marker of Arrhythmia and Ischemia Detection-A Review -- Functional Link Artificial Neural Network (FLANN) based Design of a Conditional Branch Predictor -- Development of a Model Recommender System for Agriculture using Apriori Algorithm -- Emotion Speech Recognition based on Adaptive Fractional Deep Belief Network and Reinforcement Learning -- A Change Detection Technique using Rough C-Means on Medical Images -- Autonomous Path Guiding Robot for Visually Impaired People -- Analysis of Diabetes for Indian Ladies using Deep Neural Network -- A Survey: Classification of Big Data -- Security Measures In Distributed Approachof Cloud Computing -- The Extent Analysis Based Fuzzy AHP Approach for Relay Selection in WBAN -- Fingerprint Classification by Filter Bank Approach Using Evolutionary ANN -- A sequence based Cellular Manufacturing System design using Genetic Algorithm -- Multimodal Biometrics Authentication using Multiple Matching Algorithm -- Kinship Verification from facial images using feature descriptors -- A Feature Averaging method for Kinship Verification -- An Artificial Intelligence Technique for Low Order Harmonic Elimination in Multilevel Inverters -- A Hybrid Approach to Address IP Traceback Problem using Nature Inspired Algorithm -- OEFC Algorithm - Sentiment Analysis on Goods and Service Tax System in India -- Graph Based Sentiment Analysis Model for E-Commerce websites' data -- Isolated Word Recognition based on Different Statistical Analysis and Feature Selection Technique -- Keyword Extraction from Tweets using Weighted Graph -- A novel method for Epileptic EEG classification using DWT, MGA, andANFIS: A real time application to cardiac patients with epilepsy -- Exploring hybrid recommender systems for personalized travel applications -- Aggregated Rank in First-Fit-Decreasing for Green Cloud Computing -- Real-Time Vehicle-Type Categorization and Character Extraction from the License Plates -- Ranking decision rules using rough set theory - A comparative analysis -- Performance Comparison of Clustering Algorithms based Image Segmentation on Mobile Devices -- An Enhanced Approach to Memetic Algorithm used for Character Recognition -- Performance Analysis of Extreme Learning Machine Variants with varying Intermediate Nodes and Different Activation Functions -- Role of Filter Sizes in effective Image Classification using Convolutional Neural Network -- Sentiment Analysis on Product Reviews Using Machine Learning Techniques -- Optimization of Electricity Bill on Study of Energy Audit by Using Grid Integration of Renewable Energy Sources -- Computer Aided Diagnosis of Epilepsy Based on the Time-Frequency Texture Descriptors of EEG Signals Using Wavelet Packet Decomposition and Artificial Neural Network -- User identification methods in Cognitive Radio Networks -- Design and Performance Analysis of Optical Signal Processing Module in Open Air & Underwater Environment -- Analysis of Jitter and Shimmer for Parkinson's disease diagnosis using telehealth -- Real Time Bio-Medical Recursive Images Detection Algorithm for Indian Telemedicine Environment -- Application of Multi Domain Fusion Methods for Detecting Epilepsy from Electroencephalogram Using Classification Methods -- A Cognitive Approach for Design of Smart Toilet in Healthcare Units -- A Novel Trimet Graph Optimization (TGO) topology for Wireless Networks.
Keywords: Computational intelligence; Bioinformatics; Neural networks (Computer science) .; Artificial intelligence; Computational Intelligence; Computational and Systems Biology; Mathematical Models of Cognitive Processes and Neural Networks; Artificial Intelligence